IMPLEMENTASI PEMBELAJARAN KARAKTER ANAK USIA DINI DI PAUD ANAK KITA PRESCHOOL SAMARINDA - Heppy Liana; Budi Rahardjo; Hasbi Sjamsir (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aims to (1) To obtain in-depth information about the implementation of character learning conducted in Our Children Preschool (2) To obtain information about the supporting and inhibiting factors Planting the character values in our children Preschool Samarinda. The research approach used is qualitative descriptive. Data collection includes (1) Observation, (2) In-depth interview, (3) Field Records, (4) Documentation. Data analysis techniques used interactive analysis model developed by Miles and Huberman, namely data reduction, display data, and withdrawal of conclusions / verification. The results showed: (1) Implementation of Learning Values of early childhood characters in our children Preschool is done through daily learning activities in the center and activities supporting the theme of outdoor activity with the strategy approach through exemplary by giving a good example of behavior , the nature and the way of thinking, the method of habituation by way of character plantings that are done regularly and continuously to train the child to have good habits, the method of story, that is by using a story that contains the incident experienced by a person, group, or others, advice by using advice. (2) Supporting and inhibiting factors in learning Implementation Early Childhood Character Values in Our Children Preschool Samarinda, among others, from parents, students and educators.Keywords: Character Values, Learning, Early Childhood